2014
DOI: 10.1089/thy.2013.0261
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Thyroid Dysfunction Among Pregnant Women in Lubumbashi, Democratic Republic of Congo

Abstract: Our results show that there is a high prevalence of thyroid dysfunction in pregnant women of Lubumbashi, and this high prevalence is associated with iodine deficiency. To prevent obstetrical adverse outcomes and neurological damage in children, iodine supplementation is needed before conception or in early pregnancy in Lubumbashi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
6
17
0
Order By: Relevance
“…The prevalence of hypothyroidism has been reported from different countries very recently. [ 10 11 12 ] On analysis, results of this study are consistent with recently published data from India and other countries. Previous studies conducted in Delhi reported a 14.3% prevalence of hypothyroidism during the first trimester.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of hypothyroidism has been reported from different countries very recently. [ 10 11 12 ] On analysis, results of this study are consistent with recently published data from India and other countries. Previous studies conducted in Delhi reported a 14.3% prevalence of hypothyroidism during the first trimester.…”
Section: Discussionsupporting
confidence: 91%
“…1,19 Thyroid dysfunction has been observed as the most frequent endocrine disorder in pregnant women. 5 We observed thyroid dysfunction in 19 (20.65%) pregnant women and the most common dysfunction was subclinical hypothyroidism (18,19.56%) when the upper normal cutoff value for TSH was taken 6.16 mIU/L. Assay specific reference ranges for thyroid hormones according to pregnancy trimester were unavailable for the kits used in study, so we could not classify the thyroid status accordingly in the present study.…”
Section: 15mentioning
confidence: 74%
“…In the Democratic Republic of Congo the prevalence of SCH was found to be 8% and the prevalence of isolated hypothyroxinemia was 12%. 16 In a study done on pregnant women in Teheran, Iran, the prevalence of hypothyroidism was found to be 4.2%, of which 89.1% of cases were subclinical. 17 Although the outcomes associated with SCH in pregnancy pose a huge risk for both the mother and her offspring, screening for SCH is not universally carried out in antenatal settings in Saudi Arabia.…”
mentioning
confidence: 99%